Conservative Approach versus Percutaneous Coronary Intervention in Patients with Spontaneous Coronary Artery Dissection from a National Population-Based Cohort Study - Chayakrit Krittanawong; Beatriz Castillo Rodriguez; Song Peng Ang; Yusuf Kamran Qadeer; Zhen Wang; Mahboob Alam; Samin Sharma; Hani Jneid (Reviews in Cardiovascular Medicine, 2024)
Background: Spontaneous coronary artery dissection (SCAD) is a rare and often underdiagnosed cause of acute coronary syndrome (ACS), predominantly affecting younger women without traditional cardiovascular risk factors. The management of SCAD remains a subject of debate, likely secondary to inconclusive evidence. This study aims to compare the clinical outcomes of SCAD patients treated with optimal medical therapy (OMT) versus those who underwent percutaneous coronary intervention (PCI) using a national population-based cohort. Methods: We conducted a retrospective analysis using the National Inpatient Sample (NIS) database from 2016 to 2020. The study included patients identified with SCAD using the ICD-10-CM (the International Classification of Diseases, Tenth Revision, Clinical Modification) code I25.42. We excluded individuals who did not receive PCI or coronary angiography, those who underwent coronary artery bypass grafting, and patients with incomplete records. The primary outcome was in-hospital mortality, while secondary outcomes included acute kidney injury, cardiac arrest, cardiogenic shock, use of temporary mechanical circulatory support, cost of hospitalization, and length of stay. National estimates were obtained using discharge weights, and statistical comparisons were performed using chi-square tests and linear regression. Multivariate logistic regression was employed to identify predictors of mortality and other outcomes. Results: A total of 31,105 SCAD patients were included in the study, with 10,480 receiving OMT and 20,625 undergoing PCI. Patients in the PCI group were older (mean age 64 vs. 54 years) and had higher comorbidities compared to those in the OMT group. The proportion of SCAD patients receiving PCI declined from 72% in 2016 to 60% in 2020. In multivariable analysis, PCI was associated with increased in-hospital mortality (odds ratio (OR) 1.89, 95% confidence interval (CI) 1.24–2.90, p = 0.0003), cardiogenic shock (OR 2.29, 95% CI 1.71–3.07, p < 0.0001), use of a left ventricular assist device (LVAD) (OR 3.97, 95% CI 2.42–6.53, p < 0.0001), and an intra-aortic balloon pump (IABP) (OR 2.24, 95% CI 1.63–3.09, p < 0.0001). Trends also suggested an association between PCI and cardiac arrest, extracorporeal membrane oxygenation (ECMO), and acute kidney injury (AKI). The PCI group had significantly higher hospitalization costs and longer lengths of stay compared to the OMT group (both p < 0.001). Conclusions: In this large, national cohort study, SCAD patients who underwent PCI had significantly higher risks of adverse in-hospital outcomes, including mortality, compared to those treated with OMT. These findings underscore the importance of careful patient selection and the potential advantages of conservative management in SCAD, particularly in patients without severe or unstable presentations. Further research is needed to develop evidence-based guidelines for the optimal management of SCAD.